Carbonaceous Oxygen Reduction Catalyst Formed from Phthalonitrile Derivatives Using Cobalt Chloride as Template Source. Issue 4 (1st January 2015) - Maruyama, Jun; Tanabe, Jun; Takahashi, Hiroyuki; Inoue, Hiroaki; Hasegawa, Takahiro; Iwasaki, Satoshi; Igarashi, Tatsuya; Ono, Michio
Abstract : Precious-metal-free cathode catalysts have been intensively developed for realization of the widespread use of polymer electrolyte fuel cells, although their activity and durability should be further increased. In this study, a carbonaceous catalyst for the oxygen reduction was formed using phthalonitrile derivatives (PNDs) as the carbon and nitrogen sources, and cobalt chloride as the template and active site sources by heat-treatment at 700°C. The heat-treatment of the mixture of PNDs and CoCl2 generated Co(0) aggregates or Co2 (OH)3 Cl depending on the kind of PNDs by the interaction between the PNDs and CoCl2, and the generation of the latter resulted in the development of micropores in the carbonaceous catalysts with the characteristic flaky structure and high oxygen reduction activity. The activity was enhanced by the addition of a small amount of FeCl2 . The heat-treatment at 900°C in addition to the heat-treatment at 700°C resulted in an improved fuel cell performance. The maximum power densities reached 0.25 and 0.1 W cm –2 under the supplied H2 /O2 and H2 /air at atmospheric pressure, respectively. The stability of the catalyst was improved by the two-step heat-treatment, which was associated with the local structure change around the metals.